Antecedents of secondary school students’ choices of science, technology, engineering, and mathematics career in peninsular Malaysia - Tey, Tiny Chiu Yuen (2022)
Malaysia will need eight million science, technology, engineering, and mathematics (STEM) workers by the year 2050. Despite the urgent demand, students tend to turn away from STEM careers, thus a STEM-oriented curriculum has been implemented nationwide to promote STEM education and prepare all upper secondary school students for STEM careers. However, there lacks a research-validated framework that describes students’ STEM career choice intention in the Malaysian context. Previous studies used similar variables reflected in the theory of planned behaviour (TPB) in career choice research, but they were not based on the TPB. Therefore, this study is aimed to determine factors influencing STEM and non-STEM students’ career choice intention through the TPB. The hypothesised predictors were perceived behavioural control, attitude towards career choice, subjective norms, media exposure, financial reward, and career interest. The role of the mediators (attitude towards career choice & career interest) and a moderator (streams of study) were also assessed in this study. Through proportional stratified cluster sampling, data were collected from 806 Form Four students in Peninsular Malaysia. Data were analysed using IBM SPSS Version 23 for preliminary tests. Consequently, 786 responses were retained for structural equation modelling using AMOS Version 23. Results from hypothesis testing and model validation revealed that 13 out of 23 of the hypotheses were supported by the data of this study. The main findings include (a) all proposed antecedents except career interest significantly influenced students’ STEM career choice intention in which subjective norms was the strongest predictor, (b) attitude towards career choice was the only significant mediator in the model, and (c) a significant difference in STEM and non-STEM students’ career choice was confirmed. This study concluded that the TPB-based model and specified models for STEM and non-STEM streams can be used to develop strategic initiatives for students in Peninsular Malaysia